Virological suppression among gay, bisexual, and other men who have sex with men living with HIV in Vancouver, Canada: A longitudinal cohort study from 2012-2017. - Heather L Armstrong; Julian Gitelman; Zishan Cui; Nicanor Bacani; Paul Sereda; Nathan J Lachowsky; Kiffer G Card; Jordan M Sang; Henry F Raymond; Julio Montaner; David Hall; Terry Howard; et al. (PLoS ONE, 2022)
Introduction In 2010, British Columbia (BC) implemented HIV Treatment as Prevention (TasP) as policy. We examined trends in virologic suppression and determinants of significant viremia among a prospective biobehavioural cohort of men who have sex with men (gbMSM) in Vancouver from 2012-2017. Methods Respondent-driven sampling was used to recruit sexually active gbMSM (≥16 years) who completed biannual study visits with a computer-assisted self-interview and clinical CD4 and viral load (VL) testing. We linked participant data with the BC HIV Drug Treatment Program to obtain antiretroviral dispensing and VL data. We conducted a trend analysis of VL suppression using univariable generalized estimating equation (GEE) multi-level modelling and multivariable GEE to identify factors associated with episodes of VL ≥200 copies/mL. Results Of 774 participants, 223 were living with HIV at baseline and 16 were diagnosed during follow-up (n = 239). We observed a significant trend towards reduced levels of unsuppressed VL (>200 copies/mL) from 22% (07/2012-12/2012) to 12% (07/2016-12/2016) (OR:0.87; 95%CI:0.83-0.91 for each 6-month period). Among those with at least one follow-up visit, (n = 178, median follow-up = 3.2 years, median age = 46.9 years), younger age (aOR:0.97; 95%CI:0.94-0.99, per year), ecstasy use (aOR:1.69; 95%CI:1.13-2.53), crystal methamphetamine use (aOR:1.71; 95%CI:1.18-2.48), seeking sex via websites (aOR:1.46; 95%CI:1.01-2.12), and lower HIV treatment optimism (aOR:0.94; 95%CI:0.90-0.97) were associated with episodes of elevated viremia. Conclusions During a period when TasP policy was actively promoted, we observed a significant trend towards reduced levels of unsuppressed VL. Continued efforts should promote HIV treatment optimism and engagement, especially among younger gbMSM and those who use ecstasy and crystal methamphetamine.